Various checkpoints prevent the synthesis of Staphylococcus aureus peptidoglycan hydrolase LytM in the stationary growth phase. Issue 4 (2nd April 2016) - Lioliou, Efthimia; Fechter, Pierre; Caldelari, Isabelle; Jester, Brian C.; Dubrac, Sarah; Helfer, Anne-Catherine; Boisset, Sandrine; Vandenesch, François; Romby, Pascale; Geissmann, Thomas
ABSTRACT: In Staphylococcus aureus, peptidoglycan metabolism plays a role in the host inflammatory response and pathogenesis. Transcription of the peptidoglycan hydrolases is activated by the essential 2-component system WalKR at low cell density. During stationary growth phase, WalKR is not active and transcription of the peptidoglycan hydrolase genes is repressed. In this work, we studied regulation of expression of the glycylglycine endopeptidase LytM. We show that, in addition to the transcriptional regulation mediated by WalKR, the synthesis of LytM is negatively controlled by a unique mechanism at the stationary growth phase. We have identified 2 different mRNAs encoding lytM, which vary in the length of their 5′ untranslated (5′UTR) regions. LytM is predominantly produced from the WalKR-regulated mRNA transcript carrying a short 5′UTR. The lytM mRNA is also transcribed as part of a polycistronic operon with the upstream SA0264 gene and is constitutively expressed. Although SA0264 protein can be synthesized from the longer operon transcript, lytM cannot be translated because its ribosome-binding site is sequestered into a translationally inactive secondary structure. In addition, the effector of the agr system, RNAIII, can inhibit translation of lytM present on the operon without altering the transcript level but does not have an effect on the translation of the upstream gene. We propose that this dual regulation of lytM expression, at the transcriptional and post-transcriptional levels, contributes to prevent cell wall damage during the stationary phase of growth.